Flexible Parallel Bar for Physiotherapy Purposes - Mirin, S.N.S.; Mohsin, T.M.M.; Annuar, K.A.M. (International Journal of Human and Technology Interaction (IJHaTI), 2019)
The utilization of parallel bars in rehabilitative and active recuperations is crucially critical in the medicinal services calling. Parallel bars are utilized to enable individuals to recover their quality, adjust, scope of movement, and freedom. For individuals recouping from wounds, ailments, and other crippling conditions, parallel bars are importance things of active recuperation, recovery, and exercise hardware. However, there are some obstacles while adjusting the bar height according to patient’s height. This is because the height of bar is adjusted manually by a physiotherapist. It will take time before the patient’s allowed to use it. Therefore, Flexible Parallel Bar is designed to address this problem. This design consists of a control unit that will control bar on the left and right. Control panel comprises a selection switch (left and right) and up/down button. Forward reverse motor is used to downward and upward the shaft according to the desired height. In addition, the parallel bar design is portable. This allows the family member assemble the parallel bar at home. This can save time to commute from home to a physiotherapy center where as the physiotherapy exercises can be done at home or everywhere that request by patient.